Sistema de mensuração de desempenho para estruturação do processo de aprovação de conexões de sistemas de geração distribuída em distribuidoras de energia elétrica - Freitas, Cléber Vinícius de (2021)
The priority for energy stability led studies in the electrical engineering area for a long time to implement large power plants centralized in places far from the load center, implying the construction of substations and transmission lines that increase costs sustained by expressive tariffs electricity consumers. In the last decade, a transition to new forms of electricity generation from renewable sources has been verified in the international scenario. Brazil, with its continental dimensions and characteristics, has a wide diversity of energy sources, being privileged in its nature for the generation of energy from renewable sources. To expand the use of small power plants dispersed and close to consumption points, ANEEL published Normative Resolution nº 482 in 2012. The regulation allows any consumer in the regulated contracting environment to produce its energy and, when leftovers from its self-production occur, these can be injected into the distributor’s networks to generate credits that can later be used discounting them from the monthly billing of the consumer unit. This arrangement, called net metering, linked to the new distributed energy generation systems that have greater facility and speed of installation, formed a promising technical-commercial arrangement for the electricity sector, requiring Brazilian distributors a significant volume of approval for Distributed Microgeneration and Distributed Minigeneration systems for connection to its distribution networks. This expressive volume of new entrants with power generation had an impact on the distributor’s internal processes, mainly in the technical and commercial areas, regarding to the analysis and approval of connection projects for these systems. In view of this scenario, opportunities for improvement were identified in these internal processes of the electricity distributors, which need dynamic adjustments through the identification, creation, measurement and analysis of indicators associated with a multicriteria modeling for decision making that leads the managers of the areas the application of strategies that promote greater competitiveness for the organization in this market niche.